Comparing pyrotinib with trastuzumab and pertuzumab with trastuzumab for HER2-positive metastatic breast cancer: a retrospective, multicenter analysis - You, Shuhui; Xie, Yizhao; Sang, Die; Luo, Ting; Yuan, Peng; Xu, Fei; Wang, Biyun (Frontiers in Endocrinology, 2023)
Objective: Pyrotinib and pertuzumab are effective treatment options for HER2-positive metastatic breast cancer (HER2+ MBC). Our study was to directly compare the efficacy and safety of pyrotinib plus trastuzumab (PyroH) and pertuzumab plus trastuzumab (HP) in patients with HER2+ MBC. Methods: We conducted a retrospective examination of HER2+ MBC patients who received PyroH plus chemotherapy or HP plus chemotherapy between 2017 and 2022 at five institutions in China. Our primary endpoint was progression-free survival (PFS).Results: This study involved 333 patients, among which 161 received PyroH and 172 received HP. The utilization of PyroH as a first-line therapy for MBC was more prevalent among older patients, those with a shorter duration of disease-free interval, or those who had previously been treated with trastuzumab. Although in the first-line advanced treatment HP cohort showed numerically longer PFS (median PFS: 14.46 vs. 22.90 months, p=0.057), in the second-line or later treatments, there was no significant difference in PFS between the PyroH and HP groups (median PFS: 8.67 vs. 7.92 months, p=0.286). Despite HP showing a longer PFS in the overall cohort (median PFS: 9.30 vs. 13.01 months, p=0.005), it did not serve as an independent predictor of PFS in the multivariate analysis (HR 1.134, 95% CI 0.710-1.811, p=0.598). Without taxane, PyroH demonstrated a longer PFS than HP (median PFS: 10.12 vs. 8.15 months, p=0.017). PyroH group displayed a numerically longer median PFS in patients with brain metastases compared to the HP group, though not statistically significant (median PFS: 9.03 vs. 8.15 months, p=0.976). PyroH had higher incidence of grade 3/4 diarrhea (34.3% vs. 3.0%) but similar overall adverse events.In conclusion, PyroH is comparable in second-line or later treatment and during brain metastasis, even having superior efficacy without taxane in real-world setting. Toxicities were tolerable in both groups. (ClinicalTrials.gov: NCT05572645)